Occurrence of salmonellae in retail raw chicken products in Ethiopia - Tibaijuka, B.; Molla, B.; Hildebrandt, G.; Kleer, J. (2003)
A cross-sectional study was undertaken to determine the presence and prevalence of salmonellae in retail raw chicken meat and giblets (gizzard and liver) in supermarkets in Addis Ababa (Ethiopia). A total of 301 samples (244 chicken meat, 32 gizzards and 25 livers) were collected from 22 randomly selected supermarkets and examined for the presence of Salmonella. For the isolation and identification of salmonellae, the technique recommended by the International Organization for Standardization (ISO 6579, 1998) was used. Salmonellae were detected from 54 (17.9%) of the 301 samples examined. Chicken meat and giblet samples in 68.2% (15/22) of the supermarkets were contaminated with salmonellae. The contamination level of Salmonella was higher in chicken giblets as compared to chicken meat, which were respectively 12.3%, 53.1% and 28.0% in chicken meat, gizzard and liver samples. Out of the 54 Salmonella isolates, nine different serotypes were identified: Salmonella Braenderup (31.5%), S. Anatum (25.9%), S. Saintpaul (14.8%), S. Uganda (11.1%), S. Haifa, S. Group B, S. Rough form and S. Typhimurium (each 3.7%) and S. Virchow (1.8%). The high level of Salmonella contamination of chicken meat and giblets observed in the present study indicated the need in an improvement in the microbiological quality of retail chicken in Ethiopia.